STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGEMBANGKAN BURSA KERJA KHUSUS (BKK) STUDI DESKRIPTIF DI SMK NEGERI 2 CIMAHI - R. Utami Sulistiani (Jurnal Tata Kelola Pendidikan, 2021)
This research was titled "School principal's leadership strategy in developing a special job market (BKK) descriptive study at SMK Negeri 2 Cimahi". This study aims to determine the principal's leadership strategy in developing BKK. This study uses a descriptive method of qualitative approach. The data collection technique used is interviews and documentation studies. In carrying out the duties and functions of the BKK SMK Negeri 2 Cimahi refers to the decision of the Director General of Development and Placement of Domestic Workers Number: Kep-131 / DPPTKDN / XI / 2004 concerning Technical Guidelines for Special Peterinary Exchange. In carrying out his duties of the principal referring to the function of the Goldlim (Educator, Manager, Administrator, Supervisor, Leader, Innovator, Motivator) plus the Leader of Entrepreneur. The role of edification of leadership through the Educator function, namely facilitating the BKK coordinator to attend the technical guidance of BKK management and attending a meeting between BKK Chairperson, in addition to making a cooperation MoU with the company, coordinating with the Cimahi City Manpower Office and Ministry In the implementation there are several obstacles, including the lack of staff in BKK, policies that are not in one direction, parental permission, there are still graduates who are not ready to work, the existence of companies that want to recruit do not match the majors, the limitations of the school in accessing employment information, and age The recommendations for schools, especially to develop BKK, namely schools need to re-analyt the need for employees, especially for BKK staff, the school needs to convince students' parents that the Vocational School aims to create individuals who are ready to plunge into the business world / industry and have been equipped with certain competencies. Then the school can create a culture that is similar to the business of the business world / industrial world to improve the readiness of students to work.